Oral treatment with the herbal formula B401 protects against aging-dependent neurodegeneration by attenuating oxidative stress and apoptosis in the brain of R6/2 mice - Wang, Sheue-Er (Clin Interv Aging, 2015)
BACKGROUND: Neurodegeneration is characterized by progressive neurological deficits due to selective neuronal loss in the nervous system. Huntington’s disease (HD) is an incurable neurodegenerative disorder. Neurodegeneration in HD patients shows aging-dependent pattern. Our previous study has suggested that a herbal formula B401 may have neuroprotective effects in the brains of R6/2 mice. OBJECTIVE: To clarify possible mechanisms for neurodegeneration, which improves the understanding the aging process. This study focuses on clarifying neurodegenerative mechanisms and searching potential therapeutic targets in HD patients. METHODS: The oxidative stress and apoptosis were compared in the brain tissue between R6/2 HD mice with and without oral B401 treatment. Expressions of proteins for oxidative stress and apoptosis in the brain tissue of R6/2 HD mice were examined by using immunostaining and Western blotting techniques. RESULTS: R6/2 HD mice with oral B401 treatment significantly reduced reactive oxygen species levels in the blood, but markedly increased expressions of superoxide dismutase 2 in the brain tissue. Furthermore, R6/2 HD mice with oral B401 treatment significantly increased expressions of B-cell lymphoma 2 (Bcl-2), but significantly reduced expressions of Bcl-2-associated X protein (Bax), calpain, and caspase-3 in the brain tissue. CONCLUSION: Our findings provide evidence that the herbal formula B401 can remedy for aging-dependent neurodegeneration of R6/2 mice via suppressing oxidative stress and apoptosis in the brain. We suggest that the herbal formula B401 can be developed as a potential health supplement for ameliorating aging-dependent neurodegeneration.